Evaluasi Program Gerakan Literasi Sekolah di SD Kristen 04 Eben Haezer - Kurnia Destrianto (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2021)
This study aims to evaluate the context, input, process, and product components of the School Literacy Movement (SLM) program at SD Kristen 04 Eben Haezer Salatiga. This evaluation research uses CIPP model with a qualitative description approach. The data collection was done by interview, observation and document study techniques. The data were analyzed by calculating the means of data collection, data reduction, data presentation, and conclusions. The data was validated by triangulation of sources and techniques. The results showed: (1) context: the SLM program was implemented in accordance with the emergence of Ministry of Education Regulation number 23 of 2015 in order to improve character, knowledge, and a sense of reading students, (2) the SLM program input in planning, financing and facilities, and infrastructure was in accordance with needs, but the SLM management structure has not yet been arranged. (3) process, the SLM program has been implemented in accordance with the plan. Constraints faced are in the form of lack of motivation and student interest, teachers have not received training, the view that SLM interferes with learning, and time is still lacking. (4) the product implementation of the SLM program is in accordance with the objectives but there are still things that need to be improved. So that the SLM program at Christian Elementary School 04 Eben Haezer needs to be continued the following year with improvements in several aspects.